Simulation based electrostatic study of different multigate quantumwell field effect transistors by changing the gate oxide thickness and metal work function - Afsin, Muntasirul Haque; Kabir, Shahriar; Siddiqui, Aminul Haque (BRAC University, 2017)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2016.